Achiral Dye/Surfactant Heteroaggregates for Chiral Sensing of Phosphocholines. Issue 1 (20th October 2015) - Ceccacci, Francesca; Scipioni, Anita; Altieri, Barbara; Giansanti, Luisa; Mancini, Giovanna
Abstract: An investigation, based on absorption and circular dichroism spectroscopy, was carried out on assemblies formed in water upon the interaction of heteroaggregates, composed of dyes (Congo Red or Evans Blue) and cetyltrimethylammonium bromide (CTAB), with four enantiopure phopshocholines (DMPC, DPPC, DOPC, and POPC) characterized by the same polar head and different hydrophobic tails. The results show that the nature of the lipid as well as the concentration ratios influence sensitively the absorption and chiroptical properties of the supramolecular structure. Intriguingly, the transfer of chirality from the lipid to the assembly may be triggered or not, depending on the nature of the lipid hydrophobic chain. These findings confirm the fundamental role of hydrophobic interactions in the transcription of chirality from molecules to complex architectures. Chirality 28:22–28, 2016 . © 2015 Wiley Periodicals, Inc. Abstract :